Classic drucker : essential wisdom of Peter Drucker from the pages of Harvard business review - Drucker, Peter F. [ (Peter Ferdinand)] , 1909-2005 (Harvard Business School Publishing, 2008)
This volume presents an opportunity to trace the evolution of the great shifts in organizations, and to grasp more firmly the role of managers in the ongoing effort to balance change with continuity --[book jacket]